The double trouble monster – Unmasking hidden tuberculosis in silicosis patients: A case series - S Gowri Shankar; D Suresh Kumar (Journal of Association of Pulmonologist of Tamil Nadu, 2024)
Tuberculosis occurs commonly in silicosis and is difficult to diagnose. We are presenting four cases of silicotuberculosis. The first three cases of silicotuberculosis have occupational risk factors such as borewell driller, construction sites, and quarry presented with silicotuberculosis clinic radiological features with negative sputum acid-fast bacilli and positive results for tuberculosis obtained from bronchoalveolar lavage samples. The last case developed silicosis due to inhalational burned sugarcane crops. Antituberculosis therapy started after microbiological confirmation for tuberculosis. Hence, a vigorous search of tuberculosis in silicosis patients is highly warranted.